The Origin and Early Development of the Zhou Changes - Shaughnessy, Edward (Brill, 2023)
The Zhou Changes, better known in the West as I Ching, is one of the masterpieces of world literature. This book, the climax of more than forty years of research in Chinese archaeology, explores the text’s origins in the oracle-bone and milfoil divinations of Bronze Age China and how it transformed over the course of the Zhou dynasty into the first of the Chinese classics. The book provides an in-depth survey of the theory and practice of divination to demonstrate how the hexagram and line statements of the text were produced and how they were understood at the time.